2020
DOI: 10.3390/ani10091571
|View full text |Cite
|
Sign up to set email alerts
|

Application of Effective Day Degrees in the Assessment of Stable Isotope Patterns in Developing Seahorses under Different Temperatures

Abstract: Relations between nutrient assimilation and growth rate in fishes may vary with abiotic factors such as temperature. The effects of feeding status, ontogeny and temperature regimes (15, 18 and 21 °C) on stable isotope (δ13C and δ15N) patterns were assessed in juveniles of the seahorse Hippocampus guttulatus. The use of effective day degrees (D°eff), day degrees (D°) and chronological time (age) were compared as development progress indices. Newborn seahorses were maintained at three temperature levels both dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The results from our study suggest that copepods are more efficiently assimilated by H. guttulatus juveniles than Artemia, at least during the first DAR. Initially (24-48 h), juveniles from both dietary treatments performed similarly, with δ 13 C values showing a trend similar to previous findings [31] but not related to δ 13 C values in prey. Afterwards, the trends diverged, indicating an improvement of food assimilation in both treatments.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results from our study suggest that copepods are more efficiently assimilated by H. guttulatus juveniles than Artemia, at least during the first DAR. Initially (24-48 h), juveniles from both dietary treatments performed similarly, with δ 13 C values showing a trend similar to previous findings [31] but not related to δ 13 C values in prey. Afterwards, the trends diverged, indicating an improvement of food assimilation in both treatments.…”
Section: Discussionsupporting
confidence: 85%
“…The application of stable isotopes as a nutritional tool in aquaculture represents a powerful method to assess the incorporation of nutrients from the diet into consumers [24][25][26] since the isotopic composition of animal tissues is related to that of the consumer's diet, with a slight variation named trophic discrimination [27,28]. The long-snouted seahorse Hippocampus guttulatus Cuvier 1829 is a European species whose rearing has been recently considered [12,15,[29][30][31]. As in other seahorse species, significant improvements in husbandry and rearing techniques have been recently achieved [5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the almost complete exhaustion of yolk reserves in newborn H. reidi [47] and the rapid adaptation to exogenous feeding, the juveniles undergo a fast initial change towards dietary isotopic values (e.g., copepods) [48]. Previous studies have shown that when organisms were provided with a new diet isotopically different from the previous diet, their tissues will eventually reflect the isotopic signature of the new diet [24,36,49].…”
Section: Discussionmentioning
confidence: 99%
“…Clear differences in the trophic shift were also observed within both intensive farming systems (sea cages and inland tank) (Figure 2). The temperature regime of the growth media and food deprivation due to differences on feeding frequency and quantity of the intensive systems may affect the fish isotopic values [76]. In our experimental work, the metabolic assimilation of the feed was reflected in the muscle of the fish with the characteristic trophic shift, defined as the difference between the mean muscle isotopic signature of a group and that of its respective diet.…”
Section: Discrimination Of Farming Systemmentioning
confidence: 97%
“…Clear differences in the trophic shift were also observed within both intensive farming systems (sea cages and inland tank) (Figure 2). The temperature regime of the growth media and food deprivation due to differences on feeding frequency and quantity of the intensive systems may affect the fish isotopic values [76].…”
Section: Discrimination Of Farming Systemmentioning
confidence: 99%